Reproducibility of motor unit number index and multiple point stimulation motor unit number estimation in controls. Issue 5 (15th October 2018) - Higashihara, Mana; Menon, Parvathi; van den Bos, Mehdi; Geevasinga, Nimeshan; Vucic, Steve
ABSTRACT: Introduction : Reproducibility of the multiple point stimulation motor unit number estimation (MPS‐MUNE) technique was compared with the recently developed motor unit number index (MUNIX) technique. Methods : MPS‐MUNE and MUNIX were performed on 15 healthy subjects at 3 different time‐points by the same examiner. Reproducibility was analyzed using intraclass correlation coefficient (ICC) and coefficient of variation (CV). Results : ICC values for MUNIX and MPS‐MUNE were excellent across 3 tests (0.80 and 0.77, respectively), although CV values were significantly lower for MUNIX than MPS‐MUNE ( P  < 0.01). In addition, test‐retest reproducibility was better for MUNIX, a finding largely attributable to poor reproducibility of the single motor unit action potential area. MUNIX ( R  = −0.48, P  < 0.05) and MPS‐MUNE ( R  = −0.53, P  < 0.05) were significantly correlated with age. Discussion : MUNIX demonstrated better intrarater reproducibility and may be a more reliable neurophysiological biomarker than MPS‐MUNE. Muscle Nerve 58 : 660–664, 2018